ダイ14ジ ナンキョク チイキ カンソクタイ エットウ ホウコク 1973 1974 - 平沢, 威男; ヒラサワ, タケオ; HIRASAWA, Takeo (国立極地研究所, 1975)
P(論文) The 14th wintering party of the Japanese Antarctic Research Expedition (1973-1974) consisting of thirty members was in charge of research activities at Syowa Station for the period from February 1973 to January 1974. The main programmes of the research works were the sounding rocket experiments for auroral studies, the inland traverse for the glaciological, geological, geodesical and meteorological studies and the coastal traverse for the geomorphological and geochemical studies. Seven S-210JA type rockets were fired off at Syowa Station in 1973. Objects of measurements were electron and ion densities, electric and magnetic fields, infrared emissions, auroral X-rays and radiowaves in aurora. Through the successful rocket flights, significant information to reveal the physical nature of auroras was obtained. The inland traverse party made a 85-day trip from 10 November 1973 to 2 February 1974 covering about 1,500 km in the Mizuho Plateau and Yamato Mountains area. The main object was the remeasurement of the triangular strain grid band along the parallel of 72°S set by the 10th expedition in 1969, for investigating the movement of the ice sheet. During the trip, the geodesical and geological surveys around the Yamato Mountains were also carried out. The coastal party for the geomorphological study traversed more than 3,000 km on the sea ice around the southeastern part of Liitzow-Holm Bay. The depth of the sea was measured by means of the echo sounder, and the map of the submarine topography along the Soya Coast was compiled. departmental bulletin paper